Mitigasi Krisis Pangan Dalam Al-Qur’an (Perspektif Kitab Tafsir Al-Qurtubi) - Muhammad Rifki Ramadhan; Septiawardi Septiawardi; Beko Hendro (Institut Agama Islam Sumatera Barat, 2024)
This research examines the complexities of the food crisis, which is not limited to food availability but also involves interconnected social, economic, and environmental aspects. The study aims to explore the Islamic perspective, particularly the Qur'anic commentary by Imam Al-Qurṭubī, regarding the mitigation of food crises. This research employs a qualitative method through in-depth analysis of Al-Qurṭubī's commentary, especially the story of Prophet Yusuf, in an effort to find contemporary solutions to food scarcity. The results show that the principles found in Al-Qurṭubī's commentary, such as long-term planning, effective resource management, strong leadership, and a positive outlook on crises, remain relevant in the current context. This research concludes that the Islamic perspective can make a significant contribution to building a more sustainable and equitable food system. The principles revealed in this study can serve as a reference for policymakers in formulating comprehensive strategies for mitigating food crises. These findings open up opportunities to integrate Islamic values into national food policies.